Making Sense of Civic Enterprise. Social Innovation, Participatory Democracy and the Administrative State - Wagenaar, Hendrik (PARTECIPAZIONE E CONFLITTO, 2019)
Civic enterprises (CEs) - groups of citizens, often organized as cooperatives, who produce social goods in a democratic way, responsive to local and individual needs – are a rapidly proliferating phenomenon in Europe, in fields as diverse as sustainable energy, social care and urban regeneration. Yet, we know relatively little about them. Using research on social care CEs in the Netherlands, I discuss them respectively as instances of the social economy, social enterprises and as a form of participatory democracy. CEs operate in a dense administrative environment. I show how CEs experience serious constraints from the laws, procedures, operating procedures and financial regimes of state organizations and business corporations that erode their democratic nature. I conclude that CEs suffer from a democratic paradox: although they demonstrate considerable innovative potential, this goes unacknowledged by dominant economic-political institutions.